\(\sin75\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

4 tháng 8 2019

\(\sin75=\frac{\sqrt{6}+\sqrt{2}}{4}\) mình ghi thiếu

sin75 = sin(30 + 45)

= sin30.cos45 + cos30.sin45

= 1/2 . (căn2)/2 + (căn 3)/2 . (căn2)/2

= (căn 6 + căn 2)/4.

\(\sin75\)

20 tháng 7 2016

\(sin75=\frac{\sqrt{6}+\sqrt{2}}{4}\)

nhớ k đấy

23 tháng 7 2019

a) \(\sqrt{a}+1>\sqrt{a+1}\)\(\Leftrightarrow\)\(a+2\sqrt{a}+1>a+1\)\(\Leftrightarrow\)\(2\sqrt{a}>0\)( luôn đúng \(\forall x>0\) ) 

b) \(a-1< a\)\(\Leftrightarrow\)\(\sqrt{a-1}< \sqrt{a}\)

c) \(\left(\sqrt{6}-1\right)^2=6-2\sqrt{6}+1>3-2\sqrt{3.2}+2=\left(\sqrt{3}-\sqrt{2}\right)^2\)

do \(\sqrt{6}-1>0;\sqrt{3}-\sqrt{2}>0\) nên \(\sqrt{6}-1>\sqrt{3}-\sqrt{2}\) ( đpcm ) 

30 tháng 7 2018

Giải:

\(A=\sin10+\sin40-\cos50-\cos80\)

\(\Leftrightarrow A=\cos80+\cos50-\cos50-\cos80\)

\(\Leftrightarrow A=0\)

Vậy ...

\(B=\cos15+\cos25-\sin65-\sin75\)

\(\Leftrightarrow B=\sin75+\sin65-\sin65-\sin75\)

\(\Leftrightarrow B=0\)

Vậy ...

\(C=\dfrac{\tan27.\tan63}{\cot63.\cot27}\)

\(\Leftrightarrow C=\dfrac{\tan27.\tan63}{\tan27.\tan63}\)

\(\Leftrightarrow C=1\)

Vậy ...

\(D=\dfrac{\cot20.\cot45.\cot70}{\tan20.\tan45.\tan70}\)

\(\Leftrightarrow D=\dfrac{\cot20.\cot45.\cot70}{\cot70.\cot45.\cot20}\)

\(\Leftrightarrow D=1\)

Vậy ...

17 tháng 10 2020

Câu 1:

$P=\dfrac{2x+4\sqrt x+2}{\sqrt x}$ `(đkxđ:` $x>0$)

Xét $P-6=\dfrac{2.x+4.\sqrt[]x+2}{\sqrt[]x}-6=\dfrac{2x+4.\sqrt[]x-6.\sqrt[]x+2}{\sqrt[]x}$

$=\dfrac{2.x-2.\sqrt[]x+2}{\sqrt[]x}$

$=\dfrac{2.(x-\sqrt[]x+1)}{\sqrt[]x}$

Mà $x-\sqrt[]x+1=(\sqrt[]x-\dfrac{1}{2})^2+\dfrac{3}{4}>0∀x>0$
$⇒2.(x-\sqrt[]x+1)>0∀x>0$

Mà $\sqrt[]x>0∀x>0$

$⇒\dfrac{2.(x-\sqrt[]x+1)}{\sqrt[]x}>0∀x>0$
hay $P-6>0⇒P>6∀x>0$ (đpcm)

Câu 2:

$P=\dfrac2{x+\sqrt x+1}$ (đkxđ: $x\ge0$)

Ta có $x+\sqrt[]x+1=(\sqrt[]x+\dfrac{1}{2})^2+\dfrac{3}{4}>0∀x\ge0$

$⇒P>0∀x\ge0$

Xét $P-2=\dfrac{2}{x+\sqrt[]x+1}-2=\dfrac{2-2.x-2.\sqrt[]x-2}{x+\sqrt[]x+1}=\dfrac{-2(x+\sqrt[]x)}{x+\sqrt[]x+1}$

Mà $x>0⇒\sqrt[]x>0⇒x+\sqrt[]x>0$

$⇒-2(x+\sqrt[]x)<0$

$⇒\dfrac{-2(x+\sqrt[]x)}{x+\sqrt[]x+1}<0$

$⇒P-2<0$

$⇒P<2$

Vậy $0<P<2$